[Death penalty ; This side of paradise ; Southern winds [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
Tackles death penalty; Boracay's garbage problem, land and water pollution and drugs; and Mike de Leon's film which was included in an anthology produced for the 25th anniversary of the ASEAN.
Death penalty (15 min.) -- This side of paradise (10 min.) -- Southern winds (16 min.)
VHS.
Keywords: De Leon, Mike; Capital punishment -- Philippines; Motion pictures -- Production and direction -- Philippines; Tourist trade -- Environmental aspects -- Philippines -- Boracay; Boracay (Aklan) -- Description and travel